Our Critique and Awards Program: Evaluating and Refining - Glen W. Goss (Journal of Applied Communications, 1976)
Just what is the purpose of the Critique and Awards Program? Doubtless, it depends a great deal on who you are, what you do, where you do it, and what personal experiences you and your co-workers have had with the program over how many years.